The Power Law and Dividend Yields - Erik Lüders; Inge Lüders-Amann; Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2004)
Recent research suggests that the power law is one of the most universal laws in nature and it also seems to work quite fine in economics and finance. In this paper we show that the power law explains extremely well the relationship between the value of broad-based market indices and their dividends. We also show that this relationship is consistent with declining relative risk aversion of the representative investor. Hence, the power law has a solid economic foundation.
Keywords: E44; G15; G12; 330; Power law; stock prices; dividends; co-integration; Statistische Verteilung; Börsenkurs; Aktienindex; Dividende; Kointegration; Schätzung; Welt; Zipfs law